Every Kid in the Woods: The Outdoor Education Experience of Diverse Youth. Issue 1 (April 2018) - Montero, Aracely C.; Roberts, Nina S.; Wilson, Jackson; Fonfa, Lynn
The purpose of this qualitative study was to evaluate the experience of underserved fourth-grade students participating in the National Park Service's Every Kid in a Park (EKIP) initiative through the Into the Redwood Forest (IRF) education program at Muir Woods National Monument. The project's aim was to understand the experience of underserved diverse students (i.e., race and ethnicity, gender, and Title I schools) participating during the 2015–2016 school year. The study included six teacher interviews and document review procedure of 60 student journals. The findings reveal that the EKIP exposed students to parks, the inquiry-based learning proved effective for outdoor learning, and the impact of the nature experience encouraged environmental stewardship. Implications and recommendations for further implementation of both the EKIP initiative and IRF at Muir Woods are discussed.